Gambaran Karakteristik Pasien Demam Berdarah Dengue Pada Anak di Rumah Sakit Santa Elisabeth Medan Tahun 2023 - Lumban Gaol, Rusmauli; Br Karo, Mestiana; Hasugian, Alfrand Rizal D (Innovative: Journal Of Social Science Research, 2024)
Dengue hemorrhagic fever is an acute fever condition caused by the bite of the Aedes aegypti and Aedes albopictus mosquitoes. Dengue fever is divided into four main clinical symptoms such as bleeding, high fever, hematomaglei, and manifestations of circulation failure that have the potential to develop into dengue shock syndrome, which can be fatal due to plasma leakage. This study aims to determine the characteristics of dengue hemorrhagic fever patients in children. This research uses a quantitative method using a descriptive design. The population in this study are 620 people. The sampling technique in this study uses a simple random sampling method, namely 52 respondents taken from medical record data. The research instrument is in the form of a checklist table. Data analysis in this study uses tables, chart analysis, and graph analysis. The results of the study find that the highest age of dengue hemorrhagic fever patients in children is at the age of 6–12 years with total of 32 people (61.5%), the highest education of dengue hemorrhagic fever patients in children with the number of 32 people (61.5%). It is hoped that this study can be one of theinformation about the description of the characteristics of dengue hemorrhagic fever in children and as a reference to improve health services and prevention of dengue fever cases.